The cryptography by identifying the different cryptographic algorithms in the sequence of their temporal existence and importance - MSc Waseem Saad Nsaif; MSc. Wisam Mahdi Abas; MSc. Abdullah Farhan (International Journal of Psychosocial Rehabilitation, 2020)
This research consists of basic concepts and principles of cryptography, then it moves to identify the different cryptographic algorithms in the sequence of their temporal existence and importance, to begin with, traditional cryptographic algorithms, then it turns to the corresponding cryptographic algorithms where it discusses a number of algorithms including DES, AES, Triple DES, and others. Then proceeds to identify cryptographic algorithms using the public key, and also discusses a number of them such as RSA and ECC. Although the list presented previously does not cover at all the possible possibilities for network penetration, it does clarify the area of network security concerns. Network security is complicated by some fun. Here are some of the reasons for this observation: 1- Issues of achieving security related to networks and communications are not as simple as they seem to newcomers to this field. The requirements appear quite clear, and indeed, most of the basic requirements for security are evident through their names: confidentiality, identity verification, refusal to recognize, perfectionism. However, the mechanisms used to achieve these requirements can be very complex, and their understanding may require solid logic. 2- When a person develops a protection mechanism or algorithm, he must consider all possible types of attack on his system. Often times, the resulting attack is based on a different view of protection, allowing for the exploitation of unexpected vulnerabilities in protection mechanisms. 3- In light of the previous item, we see that the procedures used to provide a service are often unclear and intuitive. At first glance, it is not clear that these measures are necessary to fulfill the security requirement for which they were set. However, the picture becomes clear after all the procedures and possibilities for breaching the established security requirement have been studied. 4- When designing the various mechanisms to achieve security, a decision must be made about where to use these mechanisms, from two perspectives: physical, that is, what are the network points that need this mechanism. Boolean, i.e. in which layer or layers should this mechanism be used. 5- Most protection mechanisms include more than one algorithm or one protocol. Most subscribers must possess some confidential information (for example cryptographic keys), which leads to questions about how this information is generated, distributed, and protected. In addition, there is a reliance on communication protocols, which sometimes complicate the development of the protection mechanism. For example, if the correct work of one of the protection mechanisms assumes that there are time limits for the transmission of the message from the sender to the receiver, then any protocol or network that offers the ability to change this time interval will make the limits imposed by the protection agent a meaningless amount, and thus the mechanism will lose Protection takes effect. We see from the above that there are many things that must be taken into consideration. This chapter provides an overview of the topics on which this thesis will be built. A general discussion will begin with network security services and mechanisms, and potential attack types that have been identified. For these mechanisms. The overall model is then developed to review network security mechanisms and services.